2017
DOI: 10.1038/srep41057
|View full text |Cite
|
Sign up to set email alerts
|

Utility of baseline, interim and end-of-treatment 18F-FDG PET/CT in extranodal natural killer/T-cell lymphoma patients treated with L-asparaginase/pegaspargase

Abstract: Positron emission tomography-computed tomography (PET/CT) is widely used for initial staging and monitoring treatment responses in Hodgkin and diffuse large B-cell lymphoma. However, its prognostic value in extranodal natural killer (NK)/T-cell lymphoma (ENKL) remains unclear. Here, we conducted a retrospective study to determine the impact of PET/CT in ENKL. Fifty-two patients newly diagnosed with ENKL were enrolled. Baseline maximum standardized uptake values (SUVmax), whole-body metabolic tumor volume (WBMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…The median follow-up time ranged from 19 to 45 months. Five studies [ 22 23 , 27 29 ] focused on the prognostic value of B-PET/CT, three studies [ 22 , 24 25 ] addressed the prognostic value of I-PET/CT performed during the 4 weeks after initial treatment, and three studies [ 21 22 , 26 ] revealed the prognostic value of E-PET/CT performed after the final treatment with an interval of 3–4 weeks. Liang et al [ 23 ] used WB3SUVmax, which represents the whole body SUVmax of 3 nodal regions (superior diaphragm, inferior diaphragm and spleen) and 10 extranodal regions (upper aero-digestive tract, skin/subcutaneous tissues, central nervous system and spinal cord, lung, myocardium, bone and bone marrow, bowel, kidney and adrenals, liver and testis) as prognostic factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median follow-up time ranged from 19 to 45 months. Five studies [ 22 23 , 27 29 ] focused on the prognostic value of B-PET/CT, three studies [ 22 , 24 25 ] addressed the prognostic value of I-PET/CT performed during the 4 weeks after initial treatment, and three studies [ 21 22 , 26 ] revealed the prognostic value of E-PET/CT performed after the final treatment with an interval of 3–4 weeks. Liang et al [ 23 ] used WB3SUVmax, which represents the whole body SUVmax of 3 nodal regions (superior diaphragm, inferior diaphragm and spleen) and 10 extranodal regions (upper aero-digestive tract, skin/subcutaneous tissues, central nervous system and spinal cord, lung, myocardium, bone and bone marrow, bowel, kidney and adrenals, liver and testis) as prognostic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 22 23 , 27 29 ] revealed the value of B-PET/CT in evaluating the prognosis for ENKTL. SUV max [ 22 23 , 27 28 ], MTV [ 22 , 27 , 29 ] and TLG [ 22 , 27 ] were used to predict PFS and OS. For SUV max , the HRs for PFS and OS were 2.78 (95% CI 1.54–5.03, p = 0.0007; χ 2 = 3.81, P = 0.28, I 2 = 21%) ( Fig 2A ) and 4.78 (95% CI 2.29–9.96, p<0.0001; χ 2 = 0.31, P = 0.96, I 2 = 0%) ( Fig 2B ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these patients, the prognostic value of SUVmax was also verified by several researches. Chang et al [ 21 ] analyzed 52 stage I to IV extranodal NKTCL patients and found that baseline SUVmax > 15.1 was a poor predictor for OS independent of other clinical features but not for PFS.…”
Section: Discussionmentioning
confidence: 99%